The Role Of Majelis Ta'lim Berkat Sidin In Improving Religious Knowledge And Social Life - Eko Nursalim; Hasan Hasan; Felina (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
This research examines the role of Majelis Ta'lim Berkat Sidin in Sangatta Utara as a non-formal educational institution in improving religious understanding and social life of the community. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The results showed that Majelis Ta'lim Berkat Sidin succeeded in deepening the religious insight of the congregation through regular recitations that discussed aqidah, sharia and morals. Interactive learning methods, such as discussion and question and answer, increase participants' understanding of Islamic teachings. In addition, the assembly contributes to social solidarity through community activities such as fundraising and social services. However, there are challenges in developing facilities and improving the competence of teachers. This study confirms the importance of Majelis Ta'lim as agents of social and spiritual change in building harmonious communities based on Islamic values.